(3GdOQ GdefVO aj PcQ CUMGH GdEeGe CMeOs - (3eMeO Hf YjSi Hf eMehO Hf cfGf GdMfHdi GdUGdMi GdcfGfis; (3CMeO Hf eMeO Hf MfHd, CHh YHO Gddg, GdTjHGfqj GdhGFdj,J (B241 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi Yehe CaVGdg , MeOkG HYXje SdWGfg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B96s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B57 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs